New Pathways for the Skin's Stress Response: The Cholinergic Neuropeptide SLURP-1 Can Activate Mast Cells and Alter Cytokine Production in Mice - Ertle, Christoph M.; Rommel, Frank R.; Tumala, Susanne; Moriwaki, Yasuhiro; Klein, Jochen; Kruse, Johannes; Gieler, Uwe; Peters, Eva M. J. (Frontiers in Immunology, 2021)
Abstract Background: The alpha7 nicotinic acetylcholine receptor (Chrna7) plays an essential anti-inflammatory role in immune homeostasis and was recently found on mast cells (MC). Psychosocial stress can trigger MC hyperactivation and increases pro-inflammatory cytokines in target tissues such as the skin. If the cholinergic system (CS) and Chrna7 ligands play a role in these cascades is largely unknown. Objective: To elucidate the role of the CS in the response to psychosocial stress using a mouse-model for stress-triggered cutaneous inflammatory circuits. Methods: Key CS markers (ACh, Ch, SLURP-1, SLURP-2, Lynx1, Chrm3, Chrna7, Chrna9, ChAT, VAChT, Oct3, AChE, BChE) in skin and its MC (sMC), MC activation, immune parameters (TNFα, IL1β, IL10, TGFβ, HIF1α, STAT3) and oxidative stress were analyzed in skin from 24h noise-stressed mice and in cultured MC (cMC) from C57BL/6 or Chrna7-Knockout mice. Results: First, Chrna7 and SLURP-1 mRNA were exclusively upregulated in stressed skin. Second, histomorphometry located Chrna7 and SLURP-1 in nerves and sMC and demonstrated upregulated contacts and increased Chrna7+ sMC in stressed skin, while 5 ng/mL SLURP-1 degranulated cMC. Third, IL1β+ sMC were high in stressed skin, and while SLURP-1 alone had no significant effect on cMC cytokines, it upregulated IL1β in cMC from Chrna7-KO and in IL1β-treated wildtype cMC. In addition, HIF1α+ sMC were high in stressed skin and Chrna7-agonist AR-R 17779 induced ROS in cMC while SLURP-1 upregulated TNFα and IL1β in cMC when HIF1α was blocked. Conclusions: These data infer that the CS plays a key role in the regulation of stress-sensitive inflammatory responses but may have a surprising pro-inflammatory effect in healthy skin, driving IL1β expression if SLURP-1 is involved.